EVALUASI KEBIJAKAN REVITALISASI PASAR TRADISIONAL DALAM MEWUJUDKAN PENGEMBANGAN EKONOMI LOKAL DI PASAR PETIR KABUPATEN SERANG - Neli Nur Laili; Riswanda Riswanda; Rina Yulianti (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2022)
ABSTRACT The revitalization of the Petir Traditional Market is a program carried out by the Serang Regency government through the Department of Cooperatives, Industry and Trade aimed at increasing local revenue and improving the economy of the community around the market. However, in its application, there are still some problems in the market in terms of supporting infrastructure and lack of socialization. This research was conducted from January to June 2021 with a descriptive qualitative approach and the data were obtained through purposive sampling. Data collection techniques were carried out by interview, observation, and documentation study. The results show that the PetirMarket revitalization program has not been optimal, as evidenced by: not maintaining order in the Lightning market, not all available facilities such as market stall are filled by traders, staff resources and market management staff are still lacking, supporting infrastructure resources are not well maintained , lack of socialization and enforcement of the mechanism for the use of market facilities to traders. As a suggestion from the results of the research, it is necessary to increase evaluation and monitoring regularly by relevant officials in order to know and monitor market activities both in terms of physical, management, economic and socio-cultural aspects, as well as the need for additional staff managing the Serang Lightning Market. Keywords: Local economy revitalization policy, traditional market,